Empowering Posyandu Cadres To Reduce Stunting Rates In Seruyan Regency In 2023 - Yuyun Nailufar; Subuh, Subuh (Jurnal EduHealth, 2024)
The prevalence of stunted toddlers in Seruyan Regency based on the 2022 nutritional status survey is 34.7%, this shows an increase of 5.4% when compared to the prevalence of stunted toddlers in 2021 of 29.3%. Empowering posyandu cadres in reducing stunting rates is an activity carried out with the aim of enabling posyandu cadres to be empowered and able to reduce stunting rates in Seruyan Regency, thereby reducing the percentage of stunting in Seruyan Regency. This research aims to determine and analyze the empowerment of posyandu cadres in reducing stunting rates in Seruyan Regency. This research is qualitative research by collecting observation, interview and documentation data. The informants who were interview subjects were 8 people, including: 2 heads of the Community Health Center, 1 nutrition officer at the Community Health Center, 1 health promotion officer at the Community Health Center, 2 Posyandu cadres, 2 mothers with toddlers. These informants were taken using a purposive sampling method, namely selecting informants who understand and are involved in reducing stunting. Data analysis in this research uses stages of data reduction, data presentation, and drawing conclusions. The results of the research show that the empowerment of Posyandu cadres in reducing the stunting rate in Seruyan Regency is because assistance to cadres in Posyandu activities is not always accompanied by Puskesmas nutrition officers and there is still a lack of understanding of cadres regarding the activities in Posyandu because cadres are only focused on one activity when serving mothers of toddlers. who came to Posnyandu. Suggestions to the Health Service to be able to add nutrition officers at the Community Health Center, so that every Posyandu activity can always be accompanied by a nutrition officer who is able to provide an understanding of nutrition to mothers who have toddlers, especially toddlers who are stunted. Apart from that, Posyandu cadres can rotate the tasks at each Posyandu, so they can understand the tasks at Posnyandu in order to reduce stunting rates.